Feast of Color : The Merzbacher-Mayer Collection. - Becker, Christoph; Bezzola, Tobia; Freeman, Judi; Jawlensky, Angelica; Merzbacher, Werner; Moeller, Magdalena M.; Rachum, Stephanie; Schädler, Linda; Stevens, Maryanne; Weinberg Staber, Margit; Zweite, Armin; Zürich (Köln : DuMont Buchverlag, 2006)
Amiet, Cuno ; Barlach, Ernst ; Bauknecht, Philipp ; Beckmann, Max ; Bill, Max ; Boccioni, Umberto ; Braque, Georges ; Brignoni, Serge ; Calder, Alexander ; Campendonk, Heinrich ; Caro, Anthony ; Cézanne, Paul ; Chadwick, Lynn ; Chagall, Marc ; Delaunay, Sonia ; Derain, André ; Dorazio, Piero ; Dubuffet, Jean ; Ernst, Max ; Exter, Alexandra ; Feininger, Lyonel ; Francis, Sam ; Freundlich, Otto ; Friesz, Emile-Othon ; Glarner, Fritz ; van Gogh, Vincent ; Goncharova, Natalia ; González, Julio ; Graeser, Camille ; Gubler, Max ; Gutfreund, Otto ; Heckel, Erich ; Hepworth, Barbara ; Herbin, Auguste ; Hofmann, Hans ; Itten, Johannes ; Janco, Marcel ; Jawlensky, Alexej von ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kokoschka, Oskar ; Kupka, Frantisek ; Lanskoy, André ; Larionov, Michail ; Laurens, Henri ; Le Corbusier ; Leger, Fernand ; Linck, Walter ; Lipchitz, Jacques ; Lipton, Seymour ; Loew, Michael ; Loewensberg, Verena ; Lohse, Richard Paul ; Luginbühl, Bernhard ; Malevich, Kasimir ; Marc, Franz ; De Maria, Nicola ; Matisse, Henri ; Mattioli, Silvio ; Miro, Joan ; Mitchell, Joan ; Modigliani, Amedeo ; Monet, Claude ; Moore, Henri ; Moser, Wilfrid ; Mueller, Otto ; Müller, Albert ; Münter, Gabriele ; Nay, Ernst Wilhelm ; Nolde, Emil ; Pechstein, Max ; Picasso, Pablo ; Popova, Liubov ; Prentice, Tim ; Renoir, Pierre-Auguste ; Rickey, George ; Riley, Bridget ; Riopelle, Jean-Paul ; Rosanova, Olga ; Scherer, Hermann ; Schmidt-Rottluff, Karl ; Segal, Arthur ; Severini, Gino ; Sisley, Alfred ; Suter, Paul ; Taeuber-Arp, Sophie ; Tappert, Georg ; Tinguely, Jean ; de Toulouse-Lautrec, Henri ; Valenti, Italo ; Vallotton, Félix ; de Vlaminck, Maurice ; Werefkin, Marianne von ; Wiggli, Oscar ; Zadkine, Ossip ; Zuñiga, Francisco
Feast of Color : The Merzbacher-Mayer Collection, Kunsthaus Zürich, Zürich, 2006-02-10. 2006-05-14
boek